Robot-Guided Evacuation as a Paradigm for Human-Robot Interaction Research - Wagner, Alan R. (Frontiers in Robotics and AI, 2021)
This paper conceptualizes problem of emergency evacuation as paradigm for investigating human-robot interaction. We argue that emergency evacuation offers unique and important perspectives on human-robot interaction while also demanding close attention to the ethical ramifications of the technologies development. We present series of approaches for developing emergency evacuation robots and detail several essential design considerations. This paper concludes with a discussion of the ethical implications of emergency evacuation robots and a roadmap for their development, implementation, and evaluation.